ANALISIS PENGARUH AUGMENTED PRODUCT DAN LOCATION TERHADAP OCCUPANCY RATE HOTEL BINTANG TIGA DI WILAYAH DKI JAKARTA - suyati Djuni Kusuma (Media Riset Bisnis & Manajemen, 2002)
The general objectve of this study was to determine the relative variable derived from called as Augmented Prodct on the one hand, and Occupancy Rate of Three Star Hotel on the other hand in DKI Jakarta, Indonesia. Primary data got from apprecials of gues hotel and its managementand apprecial of the researcher for its variable owned by them. Evently, secondary data got and came from Indonesian Association Hotel and Restaurant, Direction General of Toursim, Central Statistical Bureau, Newspapers, Magazine, Brochure and Others. For fomulation acase within this study conceming:"Should be Augmented Product Hotel Affected, Three Star Hotel in DKI Jakarta, toward rate of Occupancy?" variable analysed within this study consist of: Location, Parking, Exterior and interior structure and design, Food and beverage, Guest rooms and suites, Other meeting rooms and services. Its hypothesis as follows: The existing of Augmented Product toward Occupancy Rate. The method is used to collect data such as interview, questioners and observation. Anyway data method analysis used as Linear Regression Analysis, in which variable depence (=Y) as Occupancy Rate Hotel and free variable in which Augmented Product. The results of this study that Location, Exterior and interior structure and design, Food and beverage, Guest Rooms, and Guest Hotel, Hotel Management, researcher point that the variable parkig, it was not effet for OCR. For conlusion of this stufy referred to its hotel, in order to oon perform renovation when nature ofits Augmented Producthave less that good condition too. Because of comptetition frequently mosty tighted.